Sovereign Wealth Fund’s (Swf) Increasing Role as Bank Capital Provider to Indian Banks - Narayanan Krishna Kumar, (Indian Journal of Management and Language (IJML), 2024)
Effective advertising is crucial for the company in influencing their customers to buy their products. Since advertising is the primary way in which the company communicates with its customers, it is an area of significance for companies to focus on. In spite of numerous theoretical and empirical studies that examine celebrity endorsement on purchase intention, a more comprehensive model is required. It is in the light of this I developed Fit-for-Purpose comprising of identification, internalization and fitness dimensions, which are proposed to be strong predictors of purchase intention. The study was based on literature review. The researcher recommended and concluded that firms must keep in mind that celebrity endorsements cannot take the place of robust brand building processes. As a result, marketers should make sure that the brand being endorsed and the endorser (local or international, celebrity type, etc.) are a good match, so that the endorsements will positively influence customers’ thinking processes and generate a positive impression.